Legalising contingency fees in Malaysia / Muhammad Amin Abdullah, Siti Nur Nabilah Muhammad and Rizwana Jamal Abdul Nazar - Abdullah, Muhammad Amin; Muhammad, Siti Nur Nabilah; Abdul Nazar, Rizwana Jamal (2014)
This research paper provides for a proposal to legalise contingency fees in Malaysia. Contingency fees is a mode of payment of legal fee where payment to a lawyer will only be made upon the success of a case in court. In this paper, the researchers have provided an analysis of the legal position of contingency fees in Malaysia. Also, comparison had been made with respect to the legal position of the fees in several countries which are the United States of America, the United Kingdom and Singapore. The data that are crucial for analysis in this research was obtained from a series of interview conducted to three target groups consisting of the Malaysian Bar Council, lawyers and laymen. Finally, several recommendations are made by the researchers for the legislature in terms of regulating of the application of contingency fees by lawyers in Malaysia which might be applied by the legislature in the future if this fee is legalised.